The Diversity of Molluscs in Mangrove Ecosystem of Kendari Bay - Kaharudin, La Ode; Wahidin, La Ode (Journal of Biological Science and Education, 2020)
Changes on the mangrove ecosystem, directly and indirectly, affect the living organisms associated with it, including Molluscs. This study aimed to investigating Molluscs species in mangrove ecosystem of Kendari Bay. It is descriptive research containing facts and natures of mangrove Mollusc species. This study conducted from September to November 2020. Observing and collecting the Mollusc organisms were carried out in four mangrove ecosystems like Bruguiera, Bruguiera/Rhizophora, Rhizophora, and Avicenia.  The method used in this research was an exploring technique by collecting and counting the found Mollusks. Indicators of observing the Mollusks included morphological characteristics and environmental parameters. Three important environmental parameters, like salinity, acidity (pH), and temperature, were measured during field works using hand refractometer, pH tester, and thermometer, respectively. This research indicates about 279 individuals of Mollusks found in all zones consisting of 17 species representing two classes, Gastropod (14 species) and Bivalves (3 species). During this research, the Gastropod Mollusks found Telescopium-telescopium, Terebralia palustris, T. sulcata, Cerithideopsilia cingulata, C. alata, Nerita squamulata, Cerithidea quadrata, C. obtusa, Latirus paetelianus, Cerithium kobelti, Chicoreus capucinus, Nassarius stolatus, N. niticusis, Siphonalia varicosus. For the three species of Bivalves are Polymesoda erosa, Anadora granosa, and  Sacostrea cucullata. The both species T. sulcata and S. cucullata positively dominated all total found Gastropods and Bivalves namely 21.86% and 3.943%, respectively. The three water quality parameters measured at research stations are still on tolerance limits for the collected molluscs. Keywords:   Molluscs, Mangrove Ecosystem, Kendari Bay